Ugotavljanje zadovoljstva uporabnikov s kakovostjo storitev v slovenski splošni knjižnici - Podbrežnik, Igor (Knjižnica, 2016)
Purpose: A research was made into user satisfaction with regard to the quality of library services in one of the Slovenian public libraries. The aim was to establish the type of service quality level actually expected by the users, and to determine their satisfaction with the current quality level of available library services. Methodology: The research was performed by means of the SERVQUAL measuring tool which was used to determine the size and direction of the gap between the detected and the expected quality of library services among public library users. Results: Different groups of users provide different assessments of specific quality factors, and a library cannot satisfy the expectations of each and every user if most quality factors display discrepancies between the estimated perception and expectations. The users expect more reliable services and more qualified library staff members who would understand and allocate time for each user%s individual needs. The largest discrepancies from the expectations are detected among users in the under-35 age group and among the more experienced and skilled library users. The results of factor analysis confirm the fact that a higher number of quality factors can be explained by three common factors affecting the satisfaction of library users. A strong connection between user satisfaction and their assessment of the integral quality of services and loyalty has been established. Research restrictions: The research results should not be generalised and applied to all Slovenian public libraries since they differ in many important aspects. In addition, a non-random sampling method was used. Research originality/Applicability: The conducted research illustrates the use of a measuring tool that was developed with the aim of determining the satisfaction of users with the quality of library services in Slovenian public libraries.
Keywords: public libraries; splošne knjižnice; user satisfaction; zadovoljstvo uporabnikov; kakovost knjižničnih storitev; quality of library services; user loyalty; zvestoba uporabnikov; SERVQUAL